2013
DOI: 10.1159/000351294
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Implantation in Children Affected by Postimplant Meningitis

Abstract: This study was designed to investigate the indication and advantages of contralateral implantation after postimplant meningitis (piM). Speech perception assessment, most comfortable levels and high-resolution computer tomography were used to monitor cochlear fibrosis/ossification and clinical changes in outcomes in 5 children affected by meningitis after a variable-time post-cochlear implantation. Ipsilateral ossification was found in 3 children, 1 of whom developed delayed contralateral ossification. These ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…3 It has been reported that CI may carry a higher risk of bacterial meningitis in comparison with the general population. [4][5][6][7][8] In 2002, the United States Food and Drug Administration released a notification of receiving several reports, indicating a potential correlation between CI and the incidence of bacterial meningitis. 9 Bacterial meningitis is a critical illness with remarkable morbidity and mortality rates.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3 It has been reported that CI may carry a higher risk of bacterial meningitis in comparison with the general population. [4][5][6][7][8] In 2002, the United States Food and Drug Administration released a notification of receiving several reports, indicating a potential correlation between CI and the incidence of bacterial meningitis. 9 Bacterial meningitis is a critical illness with remarkable morbidity and mortality rates.…”
mentioning
confidence: 99%
“…Several risk factors may contribute to meningitis in CI users, including otitis media, head trauma, cochlear malformations, and cerebrospinal fluid (CSF) leaks. [4][5][6][7][8] The clinical features of post-CI meningitis do not differ from those of classical meningitis which include high temperature, headache, neck stiffness, photophobia, sickness, and vomiting. However, CI users may experience further complaints such as vertigo.…”
mentioning
confidence: 99%
See 1 more Smart Citation